'Them Two Things are What Collide Together': Understanding the Sexual Identity Experiences of Lesbian, Gay, Bisexual and Trans People Labelled with Intellectual Disability. Issue 1 (19th August 2016) - Dinwoodie, Robert; Greenhill, Beth; Cookson, Alex
Abstract : Background: Previous research aiming to understand the lives of lesbian, gay bisexual and trans (LGBT) people labelled with intellectual disabilities is limited. There are few recent studies and available findings are often contradictory and inconsistent. Method: This study aimed to explore how LGBT people labelled with intellectual disabilities experienced their sexual identities. Five LGBT people labelled with intellectual disabilities were interviewed, and data were analysed using interpretative phenomenological analysis methodology. Results: Four superordinate themes represented the following: common experiences of bullying/abuse, understanding sexualities, other's responses to intellectual disabilities and sexualities, and navigating acceptance. Conclusions: Strategies for coping with abuse maintained participant's engagement in local communities. Sexuality was often problematized by others despite being generally accepted by participants. Coming out was a continual process of decision‐making to facilitate safety and acceptance. To feel fully supported, participants desired holistic service provision sensitive to their sexuality and intellectual disability needs. Clinical and research implications are suggested.